Модель комунікативної підготовки курсантів навчальних закладів Прикордонної варти Республіки Польща - Ринденко, Наталія (Studies in Comparative Education, 2015)
У статті представлено модель професійної комунікативної підготовки курсантів навчальних закладів прикордонної варти Республіки Польща. Представлена модель передбачає органічну єдність цільового, змістового, процесуального й оціночно-результативного компонентів. Усі зазначені компоненти є взаємообумовленими і взаємозалежними, їх можливо реалізувати шляхом дотримання педагогічних умов, що забезпечують ефективність функціонування цієї моделі. В статье приведены и обобщены результаты исследования опыта коммуникативной подготовки специалистов Пограничной службы Республики Польша (методологические подходы, принципы, педагогические условия, методы, формы и т.д.) и освещены основные компоненты структурно-функциональной модели указанного процесса как методической схемы. Описанная модель дает возможность отразить логику научного поиска и средства достижения результатов решения научной задачи, направленных на разработку рекомендаций по совершенствованию методики формирования профессиональной коммуникативной компетентности младшего персонала Государственной пограничной службы Украины средствами иностранного языка. The article presents the basic results of the research of the border guards` professional communication skills training practice in the Border Guard Service of the Republic of Poland training schools (methodological approaches, principles, pedagogical conditions, methods and forms) and highlights the essential components of the structural and functional model. The components of the model are interdependent and can be realized under the pedagogical conditions which ensure the effectiveness of the model. Characterized model makes it possible to represent the logic of scientific research and the means of solving scientific tasks aimed at the development of recommendations on improving the techniques of forming professional communicative competence of the State Border Guard Service of Ukraine junior staff by means of a foreign language. Nowadays, the society`s demands to the quality of the professional communication skills training of the law enforcement officials, including border guards, increase due to the peculiarities of the border service in terms of integrated border management, and European integration and Euro-Atlantic intentions of our country. That is why there is a need for comparative cross-cultural and international researches of the European border guards` professional training best practices because of the insufficiency of such information. This article is one of the first attempts of comprehensive analysis of the European border guards’ communication skills training, by means of a foreign language. It is important and necessary in terms of finding new ways and means of intensive communication skills training, changing its content and requiring the use of innovative technologies and techniques.